Studi Mineralisasi Bijih dan Inklusi Fluida pada Endapan Emas Hidrotermal di Daerah Kalisat, Kecamatan Salaman, Kabupaten Magelang, Provinsi Jawa Tengah - , AJI SHAZIDA NABILA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
There are many valuable minerals resources, one of them is gold. As a gold producer, Indonesia has a potential of gold and other ore minerals. It happen because active magmatic zone pass through Indonesia. Study area is located in Kalisat and its vicinity, Borobudur, Magelang Regency, Central Java, Indonesia. It covered by andesitic lava, andesitic breccia of Old Andesite Formation and red limestone of Jonggrangan Formation as the lithology in this area. This location is selected as the study area because itnever been determined before. This study area also indicates has been intensively altered by hydrothermal activities. Therefore this study area also indicates that it has good potential of gold and other ore minerals. This study is aimed to know geological condition that controlling mineralization and its characteristic, the hydrothermal fluid that forming ore deposits type, and the last is decide the type of epithermal gold deposits based on mineralization and its hydrothermal fluid. There are several method that used in this study, such as petrography, polish section, slab analysis, XRD analysis,FAAAS analysis, and fluid inclusion analysis. That method are aimed to know minerals composition, alteration minerals, ore mineral and fluid hidrotermal characteristic. Based on mapping data, there are lava andesitic, andesitic breccia, red limestone as the lithology, also the presence of NE-SW and NW-SE strike slip fault that could be channel ways to hydrothermal fluid that forming alteration of minerals and mineralization. Hydrothermal alteration in this study area recognized consist of argillic with clay minerals as the key mineral and propyllitic with chlorite and epidote as key mineral. Mineralization is typically represented by pyrite, chalcopyrite, sphalerite, galena, arsenopyrite, gold, silver, hematite and covelite. There are several vein textures such as vug, comb, cockade and banded. Based on FA-AAS analysis, value of the gold and siver <1 gr/ton (ppm). Based on fluid inclusion data, there are two phase (L+V) that dominated by liquid-rich inclusion and some vapor. Highest formation temperature of ore mineral ranges between 290 and 295 oC. The result of microthermometric calculation shows the salinity of hydrothermal fluid ranges of 5.2 wt.% NaCl with forming pressure about 72.1 bar and also the depth of deposits forming are 849 meter beneath the surface. Type of gold deposit in area study interpreted as intermediate sulphidation epithermal deposit. Even though there are some gold and silver discoveries, those materials in the study area are not economically potential to be mined.